Racism And Its Effect In Green Book Film By Peter Parelly : Socilogical Approach - Wulandari, Wulandari; Efendi, Dedi; Afrillesa, Rini (Universitas Muara Bungo, 2024)
This research analyzes the types and effects of acts of racism that occur in the film Green Book. The purpose of this study is (1) to clarify the types of racism that appear in the